Economics of pain management in terminally ill pets - Brainard, Don (My University, 2020)
Pain management in terminally ill pets is an important and complex issue. Physical therapy, acupuncture, non-steroidal anti-inflammatory drugs, steroids, muscle relaxers, holistic herbs, nutraceuticals, cannabinoids, and opioids are all commonly used to manage their pain. Often, they are used in combination with each other to better control the pain level. Animal owners have the option of humane euthanasia which can be considered, when time, cost, or emotional toll goes beyond the benefit-cost value to a family. This research demonstrates how to use a pain scale to facilitate decision making when managing chronic pain. Some background on pain medications and other pain management modalities are discussed. Normally more medications, higher doses, and opioids are added when pets are in a terminal decline. The research uses a terminally ill canine with cancer in the final six weeks of his life. We employ a benefit-cost analysis using pecuniary and non-pecuniary risks and benefits to facilitate a decision guide. The pecuniary variables are cost of medications and veterinary services. The non-pecuniary costs include separation anxiety and emotional cost. The satisfaction the pet owner gets from the companionship of the pet is captured as the principal benefit in the model. The model explores alternative values for the different variables and simulates the potential decision outcomes. The decision rule using the benefit-cost ratio analysis is the traditional economic decision rule: When the benefit cost ratio is greater than unity, the pet owner may choose to continue treatment. However, a benefit-cost ratio of less than unity would require the pet owner to consider the pet’s quality of life and discuss euthanasia as an effective economic and emotional option. The benefit cost model developed in this study provides a useful tool for veterinarians to discuss the difficult subject of euthanasia with their clients when the quality of life of their terminally-ill pet does not justify sustaining life even if the pet owner’s separation anxiety seems to ignore this. The model relieves the veterinarian from making the decision for the client, and allows the client to explore the relative weights they place on the different dimensions of the model to arrive at a decision that both humane and economical.
Keywords: Pain Management; Veterinary Practice; Economics; Cost model; Humane